2022
DOI: 10.1007/s11307-022-01778-2
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory RNA:DNA Hybrids Are p53 Independently Boosted by Hyperbaric Oxygen: a Subcellular Distribution Analysis by Automated Quantitative Imaging

Abstract: Purpose RNA:DNA hybrids are co-transcriptional products with acknowledged cytoplasmic pro-inflammatory role as activators of the cGAS-STING pathway. We recently proved them also as radiation-induced senescence messages for the abscopal effect mediation, demonstrating the need for a functional p53 for their production and release in A549 and H1299 tumour cells. However, little is known about their role under different stress conditions, especially in cancer cells. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Previous studies investigating the effects of HBO‐ or H 2 O 2 ‐induced oxidative stress on human osteoblastic, HeLa, and RPE‐1 cells have reported the occurrence of single‐stranded DNA damage and RNA:DNA hybrids 61–63 . These molecular events were associated with increased activation of ATM, formation of Tp53bp1 foci, and induction of apoptosis 61–63 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies investigating the effects of HBO‐ or H 2 O 2 ‐induced oxidative stress on human osteoblastic, HeLa, and RPE‐1 cells have reported the occurrence of single‐stranded DNA damage and RNA:DNA hybrids 61–63 . These molecular events were associated with increased activation of ATM, formation of Tp53bp1 foci, and induction of apoptosis 61–63 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies investigating the effects of HBO-or H 2 O 2 -induced oxidative stress on human osteoblastic, HeLa, and RPE-1 cells have reported the occurrence of single-stranded DNA damage and RNA:DNA hybrids. [61][62][63] These molecular events were associated with increased activation of ATM, formation of Tp53bp1 foci, and induction of apoptosis. [61][62][63] Consistent with these studies, we observed increased Tp53bp1 expression at both the protein and mRNA levels in the HBO-exposed blastocysts (Figures 4K,L and 5E).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations